Place Attachment and Disaster Preparedness: Examining the Role of Place Scale and Preparedness Type. Issue 3 (April 2022) - Wallis, Amanda; Fischer, Ronald; Abrahamse, Wokje
Research shows that place attachment is associated with disaster preparedness. In two studies we examined (1) participants' place attachment at different spatial scales, (2) participants' preparedness (intentions and behaviors), and (3) place attachment as a mediator of previously identified demographic predictors of preparedness. Our findings show that place attachment is associated with both preparedness intentions and behavior. When controlling for socio-demographic predictors, participants who reported stronger house and neighborhood attachment also reported stronger intentions to prepare (Study 1). In Study 2, house attachment was associated with mitigative preparedness behavior, whereas neighborhood attachment was associated with community preparedness behavior. House and neighborhood attachment mediated the relationship between home ownership, length of residence, and preparedness. These findings suggest that place attachment varies by spatial scale which matters for different types of disaster preparedness. House and neighborhood attachment should be considered as relevant predictors of mitigative and community preparedness in at-risk communities.